The Political Economy of the Kafala Abolishment in Saudi Arabia - Rashid, Md. Mufassir (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
Saudi Arabia – an oil-rich rentier state, receives a large number of guest workers, and they were maintained under the controversial Kafala system. Recently, Saudi Arabia announced to abolish this system to come into effect in March 2021, but excluded domestic workers. Such observations show that there are political-economic incentives for the authority in abolishment apart from the humanitarian ground. Again, the current regime is willing to reduce its dependency on oil by diversifying its economy. Crown prince Mohammad Bin Salman announced massive reform plan – “Saudi Vision 2030” – to bolster FDIs and develop the public sector and service industries, where they need skilled labourers and experts to run their economy, where Kafala is not suitable. In this context, this paper would like to follow the political economy of migration policy as an analytical framework to provide a political-economic analysis of Kafala abolishment in Saudi Arabia by looking at the current transformation and Kafala abolishment.